Structure-Based Peptide Inhibitor Design of Amyloid-β Aggregation - Lu, Jinxia; Cao, Qin; Wang, Chuchu; Zheng, Jing; Luo, Feng; Xie, Jingfei; Li, Yichen; Ma, Xiaojuan; He, Lin; Eisenberg, David; Nowick, James; Jiang, Lin; et al. (Frontiers in Molecular Neuroscience, 2019)
Many human neurodegenerative diseases are associated with amyloid fibril formation. Inhibition of amyloid formation is of importance for therapeutics of the related diseases. However, the development of selective and potent amyloid inhibitors remains challenging. Here based on the structures of A fibrils and their amyloid-forming segments, we designed a series of peptide inhibitors using RosettaDesign. We further utilized a chemical scaffold to constrain the designed peptides into β-strand conformation, which significantly improves the potency of the inhibitors against A aggregation and toxicity. Furthermore, we show that by targeting different Aβ segments, the designed peptide inhibitors can selectively recognize different species of Aβ. Our study developed an approach that combines the structure-based rational design with chemical modification for the development of amyloid inhibitors, which could be applied to the development of therapeutics for different amyloid-related diseases.